Formation of Hierarchical Architectures with Dimensional and Morphological Control in the Self‐Assembly of Conjugated Block Copolymers. Issue 2 (11th November 2019) - Wang, Meijing; Han, Liang; Zhu, Yulin; Qi, Rui; Tian, Leilei; He, Feng
Abstract: Precise control of dimensionality and morphology is a crucial requirement for realizing complex and hierarchical assembled structures, which has mainly been studied in highly crystalline systems. However, such results have rarely been reported in the self‐assembly of conjugated block copolymers with relatively weak π–π interactions. Herein, the realization of unique scarf‐like self‐assembled architectures based on the conjugated block copolymers through a facile one‐step approach is reported. Dimensional and morphological control of the micelles are realized by adjusting the block ratio and the solvent polarity. Then the transformation from 1D nanorods to the final hierarchical scarf micelles is observed. Furthermore, the underlying growth mechanism is mainly attributed to the driving force of intermolecular π–π interactions between conjugated core blocks. This work provides a highly effective strategy to prepare hierarchical architectures circumventing those multistep methods used in traditional crystallization system, which could expand the morphological diversity of self‐assembly and further facilitate the exploration of its functional applications. Abstract : The construction of the hierarchical scarf‐like self‐assembled architectures based on conjugated block copolymers PPV7 ‐ b ‐P2VP n are successfully realized through a facile one‐step approach. Dimensionality and morphology are tuned by adjusting the block ratio of block copolymers and the solvent polarity. The evolvement of 1D nanorods in the final hierarchical micelles is successfully observed.